Pandemic and Enterprise Management Innovation: A Scientometric Analysis Based on the Web of Science Core Database - Kangxin Yu; Wei-fan Chen; Tianming Ning; Jinzhao Yang; Cuiyin Yao; Tian Xie (SAGE Open)
The major epidemics, especially COVID-19, caused a significant impact on global businesses, including lockdowns, labor shortages, price increases, disrupted supply chains, and increased demand. They brought challenges to enterprise systems and business modes and triggered knowledge innovations. Bibliometric and Latent Dirichlet Allocation (LDA) were used to investigate the distribution of literature, co-citation, research hotspots, and trends in pandemic-triggered enterprise management from 2006 to 2023 based on the Web of Science databases. The results show that during the outbreak period, supply chain resilience management, enterprise technological innovation and sustainable development were hot topics in research. In the post-epidemic era, enterprise crisis management and sustainable development are gradually refined, and resilience, digitalization, and sustainability will become the frontier topics.